Short term effects of the different sources of protein on renal function in the early stage of chronic renal insufficiency - Montañano, Donna P.; Panlasigui, Leonora N. (2000)
Glomerular hypertension has been established by numerous studies as the single most important factor causing progressive deterioration in renal function in patients with less than 50% residual function. Restriction of protein intake is a very effective way of minimizing increase in glomerular pressure in renal diseased patients, thus preserving renal function. To determine whether different proteins will have different effects in the glomerular pressure in patients with chronic renal insufficiency, three groups of patients with similar demographic and clinical profile were randomly assigned to three protein test meals. Changes in glomerular pressure were determined after intake of different protein meals namely mixed, pork, and fish in twelve subjects with chronic renal insufficiency (CRI) whose glomerular filtration rate (GFR) ranged from 25% to 50%. Measurements/assessments of GFR, endogenous creatinine clearance (ECC), and other indirect parameters such as total protein excretion (TPE), serum creatinine and BUN were used to assess changes in glomerular pressure. Results showed that the different protein meals demonstrated varied GFR responses. Enhanced glomerular hypertension and hyperfiltration was shown in 50% of subjects (n=2) from both mixed and pork protein meal groups. Subjects in the mixed protein meal increased their GFR (19% to 51%) and TPE (66% to 96%), while subjects in the pork meal showed an increase in ECC (17% to 48%) and TPE (42% to 67%). There was less evidence of intraglomerular hypertension in the fish meal group in the subjects (n=2) as shown by increase in ECC (8% and 9%), decrease in serum creatinine (11% and 13%) and a mild increase (5%) in TPE. Results of the amino acid analysis of the different protein meal showed differences in amino acid concentrations. Pork had higher concentrations of eight amino acids (histidine, 57%; methionine, 28%; asparagines, 19%; lysine, 19%; alanine, 15%; valine, 15%; threonine, 15%; and tyrosine, 14%) compared with fish. On the other hand, fish had higher protein content than pork. Mixed protein meal contained higher concentrations of serine, proline, and arginine compared with pork and fish. Correlation, however, between amino acids and GFR response was not established because of statistically small sample size. Pork and mixed meals may aggravate the increased glomerular pressure, while, fish may have less effect. Therefore, pork and mixed protein may hasten the decline of renal function to renal failure. Statistical significance of results was not established because of small sample size. Larger studies are required to definitely establish the effects of protein sources in intraglomerular hypertension and hyperfiltration.
Thesis (M.S. Nutrition)--University of the Philippines, Diliman.
Keywords: Proteins in human nutrition; Glomerular filtration rate; Renal manifestations of general diseases